IMAM ABU HAMID GHAZALI'S THOUGHTS ABOUT THE PERFECT MAN - Ikrom Jomuradov (Web of Journals Publishing, 2024)
In the article, the development of students in all aspects, raising their spiritual-moral, intellectual potential in accordance with world standards, especially science and enlightenment in ensuring the development of future highly educated specialists as well-rounded people The contents of the works of the famous philosopher Muhammad Abu Hamid Ghazali, who made a worthy contribution to civilization, was one of the great sages of the Eastern Renaissance, possessor of religious and worldly knowledge, served the development of tawhid, kalam, tafsir, and hadith science.
Keywords: spirituality, enlightenment, morality, pedagogical vision, value, integration, high moral virtue.